Dividend versus investment: Cash flow allocation - Elżbieta Bukalska; Anna Maziarczyk; Kinga Ociesa (Journal of Banking and Financial Economics (JBFE), 2022)
The aim of the article is to find out about the pattern in which operating cash flows are allocated between dividends and investment. We analyzed 419 companies from the Warsaw Stock Exchange and covered the period of 2007-2020 with 4,760 firm-year observations. We prepared regression models for the dividend and investment ratio depending on the company specificity. We found a positive relation between dividends and investment. Additionally, we found that with the increase of operating cash flow, both dividends and investment increase. We think that the best explanation of our findings lies in the free cash flow hypothesis and signaling theory of dividends. Dividends and investment might be a tool to mitigate managerial decisions and at the same time a tool to send a positive signal to the investor about the present and future good financial situation. The results contribute to the literature on firms' investment- and dividend-cash flow sensitivity and the order of decisions: in a residual dividend policy, investment decisions are made first and the remaining profit is paid out as dividends while another theoretical approach implies that firms decide first on their dividend level, and then make investment decisions as they are reluctant to cut dividends.
Keywords: D25; G32; G33; 330; cash flow; dividend; investment; corporate investment; dividend payouts